ANALISIS KAPASITAS SALURAN DRAINASE DAN PENANGANAN BANJIR DI JALAN BUMI AYU DESA SANUR KECAMATAN DENPASAR SELATAN - Kesuma, I Made sutrisna Ari; Yekti, Mawiti Infantri; Purbawijaya, Ida Bagus (Jurnal Ilmiah Teknik Sipil, 2021)
Flooding is a condition where excess capacity of water cannot be accommodated. It makes the water overflow to the right and left sides of the embankment of the drainage channel that causes adverse inundation. Flood phenomenon is absolutely inseparable from0the contribution0of the physical0condition0of an area from the0topography of an area where the land is gentler than0the0surrounding land. These problems occur in the drainage channel located on Jalan Bumi Ayu Denpasar. This study was aimed to deal with flooding by evaluating the capacity of the existing channel and increasing the channel on Jalan Bumi Ayu Denpasar. The analysis of drainage channel capacity in calculating rainwater discharge by observing flow patterns and channel dimension planning based on surveys that have been conducted. The annual maximum daily rainfall data was obtained from the Regional Office of the Meteorology and Geophysics Agency in Region III Denpasar. The rainfall stations reviewed were Sanglah Station and Sumerta Station. It starts with analyzing the annual maximum daily rainfall data so that the Intensity Duration Frequency (IDF) curve was obtained. Calculation of time concentration is calculated using the Kirpich formula, then the theoretical plan flood discharge was carried out by the Rational Method, namely Qt = 0.278.C.I.A and channel capacity was calculated by the formula Qsal = A.V. If the calculation results show Qsal> Qt, then the area is safe from inundation / flood problems. From the results of the analysis, the tertiary drainage could not accommodate theoretical discharge for the return period of 2 and 5 years, on the secondary channel it was unable to0accommodate0theoretical discharge0for the return0period of 5 and 10 years. So it is necessary to increase0the channel capacity0dimensions from SBA 1 to SP 4  (B: 0,75 - 1; H: 0,9 - 1,7) m.